Nutritive value of selected forages on the coastal region rangelands of Tanzania (Makerere University Journal of Agricultural & Environmental Sciences, 2001)
Although the nutritive value of forage species is of paramount importance to livestock production, it is largely unknown for most rangelands of East Africa. A study was carried out on a rangeland area west of the Ruvu floodplains, Bagamoyo district, coastal Tanzania to determine the nutritive value of palatable herbaceous species. The commonly occurring palatable grasses (at their flowering stage) and browse species were analysed for crude protein (CP), crude fibre (CF) and major mineral elements (calcium, magnesium and phosphorus). The forage species analysed were Urochloa mosambicensis, Panicum maximum, Panicum parvifolium, Eragrostis superba, Sporobolus pyramidalis (grasses), Commiphora africana and Pteleopsis myrtifolia (browse). The species had adequate levels of crude protein (grass: 8.65₺2.15%; browse: 13.61+2.26%), crude fibre (grass: 35.98+5.15%; browse: 19.17+3.64%), phosphorous (grass: 0.2310.13%; browse: 0.18t0.01%), calcium (grass: 0.25+0.10%; browse: 0.4910.11%), Ca:P ratio (grass; 1.0:1.0 - 5.6:1.0; browse: 1.79:1.0 - 3.68:1.0), and magnesium ( grass: 0.3610.11%; browse: 0.33+0.01%) to support the growth and maintenance of livestock. Their CP, CF and mineral contents were significantly different, with browse having highest nutritive value. P. maximum, P. parvifolium, Urochloa mosambicensis, Sporobolus pyramidalis, and E. superba were significantly different in their %CP (P
Keywords: Animal Production; Crude fiber; Crude protein; mineral nutrients